Mottainai - Japanese Ancient Mantra in combating COVID-19 - Azizul Helmi, Sofian (2021)
For more than a year, our country has been combating COVID-19, the number of infections is still high and worrying. National Recovery Plan remains in phase one, and everybody was asked to stay put at home unless for essential activities. This movement control still needs to be implemented to curb the virus. In addition, the new variants of Alpha, Beta, and Delta, which are more contagious, have urged the government to tighten the standard operating procedures (SOP).